Nutrition Knowledge, Dietary Pattern, and Nutritional Status of Elementary Students in Makassar City - Syarfaini Syarfaini; Eka Sari Ridwan; Syahratul Aeni (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Elementary school children are a vulnerable group to nutritional problems. Malnutrition is generally caused by poverty, lack of food supplies, poor environmental quality, lack of public knowledge about nutrition, a balanced diet, and health. The purpose of this study was to analyze the relationship between balanced nutrition knowledge, dietary pattern, and nutritional status of children in Sekolah Dasar Islam Terpadu (SDIT) Makassar, Indonesia. The population in this study were all students in grades 4 and 5 with a total sample of 94 people. The results showed that there was no relationship between balanced nutrition knowledge and nutritional status (P = 0.397) and there was no relationship between diet pattern and nutritional status (P = 0.662) children at SDIT Makassar. Researchers recommend a Balanced Nutrition Ambassador program in every school. Ambassadors of Balanced Nutrition will be trained related to balanced nutrition and is responsible for disseminating balanced nutrition messages to their friends and their family